Outbreak of Extended-Spectrum Beta-Lactamase Producing Enterobacter cloacae with High MICs of Quaternary Ammonium Compounds in a Hematology Ward Associated with Contaminated Sinks - Chapuis, Angélique; Amoureux, Lucie; Bador, Julien; Gavalas, Arthur; Siebor, Eliane; Chrétien, Marie-Lorraine; Caillot, Denis; Janin, Marion; de Curraize, Claire; Neuwirth, Catherine (Frontiers in Microbiology, 2016)
Objective To investigate an outbreak of extended-spectrum beta-lactamase (ESBL) producing Enterobacter cloacae that occurred in the Hematology ward (24-bed unit) of the François Mitterrand University Hospital (Dijon, France) between January 2011 and December 2013. The outbreak involved 43 patients (10 infected and 33 colonized). Design We performed environmental analysis to detect multiresistant E. cloacae for comparison with clinical isolates (genotyping by pulsed-field gel electrophoresis and MLST as well as ESBL-typing) and determined the MICs of the quaternary ammonium compounds (QACs) alkyldimethylbenzylammonium chloride (ADBAC) and didecyldimethylammonium chloride (DDAC). A bleach-based cleaning-disinfection program was implemented in December 2012 after mechanical removal of the biofilm in all sinks. Results We have detected 17 ESBL-producing E. cloacae in patients sink drains, shower drains and medical sink drains. Sequencing of the bla genes performed on 60 strains recovered from patients and environment (n=43 clinical and n=17 environmental) revealed that bla CTX-M15 was predominant (37 isolates) followed by bla CTX-M9 plus bla SHV-12 (20 isolates). We observed a great diversity among the isolates: 14 pulsotypes (11 STs) in clinical isolates and 9 pulsotypes (7 STs) in environmental isolates. Six pulsotypes were identical between clinical and environmental isolates. MICs of the quaternary ammonium compounds widely used for disinfection were very high in clinical and environmental isolates. Immediately after the implementation of the disinfection program we noticed a substantial fall in cases number. Our findings demonstrate the role of drains as important reservoir of ESBL-producing E. cloacae and highlight the necessity to settle drains accessible to achieve correct cleaning as well as to use disinfectant with proved activity against nosocomial pathogens.